[Memo from T. Donahue to S. Stuntz discussing Boston AFL-CIO dinner] (Tufts Archival Research Center, 2007)
Marginalia; Memo from Tom Donahue to Susan Stuntz discussing his attendance at a Boston AFL-CIO dinner. Describes contacts with AFL-CIO officials. Discusses upcoming meeting regarding the promotion of the issue of indoor air quality.